PENGUJIAN KESUKSESAN IMPLEMENTASI ERP (ENTERPRISE RESOURCE PLANNING) MENGGUNAKAN MODEL DELONE DAN McLEAN YANG DIPERBAHARUI PADA PT SARI HUSADA GENERASI MAHARDHIKA - Siti Rahmi (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2017)
This study aims to testing and obtain empirical evidence implementation of EnterpriseResource Planning (ERP)PT Sari Husada Generasi Mahardhika Yogyakarta using the updatedDeLone and McLean model. Delone and McLean model is a model of successful testing ofinformation technology system that are based on processes and causal relationshipof thedimensions of the model. The dimensions of this model are quality system, information quality,system usage, user satisfaction and net benefits.The research method is quantitative method of mail survey methods to company officialswho daily use the ERP. This study uses version 2.0 SmartPLS program assitence as a tool to testhypotheses in the study.Based on the results of data analysis, in getting that all constructs in this study has fulfilledthe requirements of validity and reliability. Where to terms of validity, the value of loading factormust exceed 0,7 and its reliability requirement given the level of Cronbach’s Alpha above 0,7.Based on the results of hypothesis testing shows there are several hypothesis are supported, suchas HI,HI2,H3,H5,H6,H8. And there are also the hypothesis that are not supported, for exampleH4,H7,H9.Keywords : Enterprise Resource Planning (ERP), Delone and McLean updated model, the successmodel in information technology system.